1993
DOI: 10.1159/000247341
|View full text |Cite
|
Sign up to set email alerts
|

Bimodality in Age of Onset of Psoriasis, in Both Patients and Their Relatives

Abstract: The ages at onset of 245 female and 211 male psoriasis (Ps) patients were recorded. The distribution of age of onset in both sexes is bimodal, with separation at the age of 40 years into an early-onset group and a late-onset group. These distributions were normal (Gaussian) with equal variances. These data are compatible with the hypothesis that there are two genotypes for Ps. Further evidence for this hypothesis is provided by the relationship between age of onset and number of affected relatives. The latter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 7 publications
2
29
0
2
Order By: Relevance
“…These patients have an irregular disease course, which shows a strong tendency to become generalized and severe [3, 35]. These findings, as well as the strong association of early-onset psoriasis with HLA-Cw6 [35,36,37], has led some investigators to postulate that there are in fact two separate types of psoriasis [32]. The results of our study would certainly lend indirect support to this idea.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These patients have an irregular disease course, which shows a strong tendency to become generalized and severe [3, 35]. These findings, as well as the strong association of early-onset psoriasis with HLA-Cw6 [35,36,37], has led some investigators to postulate that there are in fact two separate types of psoriasis [32]. The results of our study would certainly lend indirect support to this idea.…”
Section: Discussionsupporting
confidence: 59%
“…It is probable that the higher prevalence of a family history of psoriasis in our study (49.6%) can be accounted for by the fact that patients with mild psoriasis were excluded, rather than geographical differences; another Spanish psoriasis study reported a family history of psoriasis in 28% of patients [3]. This and other studies also found that the frequency of a family history of psoriasis was inversely related to the age at onset of psoriasis [3, 24,32,33,34]. The prognosis for patients with an early onset of psoriasis, generally those with a family history, is poor.…”
Section: Discussionmentioning
confidence: 54%
“…More than 80% of cases are plaque psoriasis vulgaris 3 and most patients are of working age 4,5 . It is a disease which is rarely fatal, which waxes and wanes, and for which there is no known cure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It affects people of all ages, and its incidence peaks in early adult life (20s) and then again in later adult life (50s and 60s). [3][4][5][6] Clinical manifestations of psoriasis are heterogeneous, ranging from limited disease to very extensive disease. Presentations of the skin lesions vary throughout life, and there may be periods of remissions and exacerbations.…”
mentioning
confidence: 99%